Primary Diffuse Leptomeningeal Melanomatosis in a Child with Extracranial Metastasis: Case Report - Shubin W. Shahab; Prabhumallikarjun Patil; Jason R. Fangusaro; Brooke Patteson; Adam Goldman-Yassen; Bree R. Eaton; William Boydston; Matthew Schniederjan; Dolly Aguilera (Current Oncology, 2024)
Primary meningeal melanomatosis is an extremely rare tumor with very few documented responses to treatment. A 3-year-old male with a complex past medical history, including prematurity and shunted hydrocephalus, was diagnosed with primary meningeal melanomatosis with peritoneal implants. Molecular testing revealed an NRAS Q61R mutation. The patient received proton craniospinal radiation followed by immunotherapy with nivolumab (1 mg/kg) and ipilimumab (3 mg/kg) IV every 3 weeks and, upon progression, he was switched to a higher dose of nivolumab (3 mg/kg IV every 2 weeks) and binimetinib (24 mg/m2/dose, twice a day). The patient had significant improvement of CNS disease with radiation therapy and initial immunotherapy but progression of extracranial metastatic peritoneal and abdominal disease. Radiation was not administered to the whole abdomen. After two cycles of nivolumab and treatment with the MEK inhibitor binimetinib, he had radiographic and clinical improvement in abdominal metastasis and ascitis. He ultimately died from RSV infection, Klebsiella sepsis, and subdural hemorrhage without evidence of tumor progression. This is the first report of a child with primary meningeal melanomatosis with extracranial metastatic disease with response to a combination of radiation, immunotherapy and MEK inhibitor therapy.